AI-Enabled Digitalization and Environmental Practices in Municipal Waste Management: Pathways to Climate Sustainability in Pakistan - Muhammad Ahsan Iqbal; Asifa Muhammad Sabir; Kundan Kumar; Md Mahfujul Islam (Environmental Management, 2026)
Rapid urbanization and the intensifying pressures of climate change have elevated solid waste management (SWM) as a critical public service challenge. Evidence on the joint mediating effects of digital transformation and environmental governance between municipal SWM and climate sustainability remains questionable. This study examines the role of SWM in promoting climate sustainability by evaluating environmental management practices and AI-enabled digitalization. Data were collected from 406 employees across seven Water and Sanitation Service Companies (WSSCs) in Khyber Pakhtunkhwa, Pakistan, using a cross-sectional survey with a structured and validated instrument. The analytical approach involved Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with bootstrapped mediation analysis (5000 resamples), executed in SPSS and AMOS software. The study measured waste management effectiveness, environmental practices, AI-enabled digital systems, and sustainability outcomes across economic–environmental–social nexus. Findings reveal a significant positive relationship between effective SWM and climate sustainability (β = 0.41, p < 0.001). Environmental practices including regulatory compliance, pollution control, and workforce training along with AI-driven digital capabilities including real-time tracking, route optimization, electronic service reporting, and data dashboards play a strong mediating role (indirect effects: ENV = 0.13; DIG = 0.12; joint = 0.21). The results suggest that municipal waste systems achieve greater climate benefits when routine operations are supported by integrated environmental management and smart digital technologies. The study contributes to the research on sustainable models, circular economy, and smart urban governance, offering policy guidance for municipal authorities in Pakistan, through AI-enabled tools and solutions, environmental governance practices, and SDG-aligned incentives.